2005
DOI: 10.2190/lk3g-8yhb-hyyl-811c
|View full text |Cite
|
Sign up to set email alerts
|

How Do Primary Care Clinicians Manage Childhood Mood and Anxiety Syndromes?

Abstract: Active management of childhood mood and anxiety syndromes in primary care was uncommon in the United States, Puerto Rico, and Canada in the mid-1990s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Unfortunately, the promise of the primary care setting in the recognition and management of pediatric psychopathology is yet to be fully realized, particularly for children and adolescents suffering from emotional disorders (Wren, Scholle, Heo, & Comer, 2003, 2005). Long‐standing cultural beliefs and expectations regarding the nature of psychopathology and its relevance to traditional medicine have likely interfered with the implementation of truly integrated care.…”
Section: Unexplained Symptoms In Pediatric Practice: Conceptual Challmentioning
confidence: 99%
“…Unfortunately, the promise of the primary care setting in the recognition and management of pediatric psychopathology is yet to be fully realized, particularly for children and adolescents suffering from emotional disorders (Wren, Scholle, Heo, & Comer, 2003, 2005). Long‐standing cultural beliefs and expectations regarding the nature of psychopathology and its relevance to traditional medicine have likely interfered with the implementation of truly integrated care.…”
Section: Unexplained Symptoms In Pediatric Practice: Conceptual Challmentioning
confidence: 99%
“…A study in the United States showed that even when mood or anxiety disorders were identified in primary care, young patients were not particularly likely to receive counselling in this setting, but instead tended to be referred to specialised services (Wren et al, 2005). A study in the United States showed that even when mood or anxiety disorders were identified in primary care, young patients were not particularly likely to receive counselling in this setting, but instead tended to be referred to specialised services (Wren et al, 2005).…”
Section: Identifying Child Mental Health Problems In Primary Carementioning
confidence: 99%
“…Of the 15 included studies, seven were conducted in the United States [16,17,21,24,26,29,30], three in the Netherlands [20,27,28], two in France [18,19], and one each in the UK [25], Croatia [22] and Australia [23]. Most studies had a cross‐sectional design [16–28], only two studies had a longitudinal design [29,30]. Four studies [20,23,27,28] used a qualitative method for the measurement of determinants of anxiety care and its improvement.…”
Section: Resultsmentioning
confidence: 99%